Integration of ICT in Classroom: Perception of University Teachers and Students - G.C. , Prem Bahadur (Myagdi Guru, 2022)
Information and Communication Technology plays a significant role in promoting educational sector including teaching and learning. Quality in education demands intensive use of ICT. The main objective of this study is to explore the perception of teachers and students regarding the use of ICT in teaching and learning. Besides, it attempts to identify the barriers and challenges faced by the teachers and the students in using ICT. Using qualitative methods of study, it gathers insights through interviews to explore their perceptions of ICT use in teaching and learning. The data have been analyzed to extract common themes and divergent viewpoints. The findings reveal that both teachers and students recognize the significant benefits of ICT in enhancing learning and teaching processes showing a significant disparity in ICT access and usage, influenced by factors like infrastructure, financial constraints, technical issues, training, and levels of ICT literacy. The study emphasizes the transformative potential of ICT in teaching and learning, alongside the necessity to enhance ICT infrastructure, training programs, and policy initiative to bridge the digital divide and promote equitable educational opportunities. This study offers practical implications for policymakers, educators, and technologists, enhance technology assisted environments effectively and inclusively.